Uji Toksisitas Letal dan Subletal Logam Berat Merkuri (Hg) Terhadap Ikan Nilem (Osteochilus hasselti) - Norman Arie Prayogo; Atik Hidayati; Asrul Sahri Siregar; Yunasfi Yunasfi (Journal Omni-Akuatika, 2016)
Mercury (Hg) is a heavy metal could pollute the river. Hg impacts on aquatic organism chronically. The influence of chemical toxic on aquatic organisms could be determined using toxicity (lethal and sublethal) tests. Osteochilus hasselti could be an object for toxicity test. A research, aiming to find LC50-96h concentration, was to find letal and subletal effects of Hg on erythrocyte and hematocryte changes. An experimental method applied Completely Randomized Design. The research was devided into 3 stages, i.e. preliminary, lethal toxicity (LC50-96h) and sublethal toxicity tests, in triplicates. Sampling of sublethal test was performed after an exposure time of 96 h (4 days) and 288 h (12 days). Lethal toxicity test data were analyzed as probit and data from sublethal toxicity test were F-tested. The result showed that LC50-96h of Hg on Osteochilus hasselti was 0.39 mg/L. The sublethal effect of Hg decreased erythrocyte ad hematocryte counts in parallel with increasing its concentration and its exposure time.Keywords: Hg, toxicity, LC50-96 hours, erythrocytes, hematocrits.